Analisis Komparatif Hasil Tangkapan Ikan Nilem (Osteochilus hasselti) di Danau Buyan dan Danau Tamblingan, Bali - Effendi, Irvan Ryan; Restu, I Wayan; Negara, I Ketut Wija (Current Trends in Aquatic Science, 2023)
Potential fish resources found in Lake Buyan and Lake Tamblingan have a similar variety of species and one of them is bony lip barb fish. This study aims to determine the percentage of the number of catches, differences in total length and weight characteristics, sex ratio, gonad maturity level (GML), the relationship between length and weight, and condition factors on bony lip barb fish (Osteochilus hasselti) caught in Lake Buyan and Tamblingan Lake. The total length of bony lip barb fish from Lake Buyan ranged from 161.00 – 224.00  mm and Lake Tamblingan ranged from 142.50– 220.10  mm. The weight of bony lip barb fish from Lake Buyan ranged from 49.20 – 121.25 grams and from Lake Tamblingan it ranged from 48.21 – 121.07 grams. Male bony lip barb fish dominating in GML III. While in female bony lip barb fish, dominating GML II. In Lake Buyan, the value of b as a result of the relationship between length and weight of bony lip barb fish is 2.76. At Tamblingan Lake, the numbers are not much different from the b value of 2.53. The relationship between length and weight of bony lip barb fish is negative alometric. The condition factor for bony lip barb fish in Buyan Lake obtained an average value of 1.01. In contrast, at Tamblingan Lake the condition factor value for bony lip barb fish caught had an average value of 1.01. Condition factors that exist in Lake Buyan and Lake Tamblingan are good water conditions with thin fish conditions